The Monitoring Photography and its Obstacles in Invertebrate Taxonomic Studies in Sumatra: A Case Study of Dragonflies (Odonata) and Water Mites (Acari) - Rijal Satria; Nela Berliani; Sandi Fransisco Pratama (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
The use of photographic methods has become an alternative approach for monitoring the diversity of invertebrate species. However, this method has inherent limitations when applied to taxonomic studies. The present study aims to discuss the future challenges in the application of photographic methods and taxonomic study of invertebrates, in the case of dragonflies and water mites. This study is descriptive study, and the data collected by using photographic methods. The result of this study is collected six species, six genera and five families of dragonflies in the river of Guguak, Kayu Tanam Sub-district, Padang Pariaman District. However, we also found the water mites in certain species, then discussed its taxonomical problems. We concluded that the application of photographic methods may affect the quality of research outcomes, particularly in studies of invertebrate animals.